Mô hình tăng trưởng và xu hướng nghiên cứu về hướng nghiệp ở trường phổ thông từ 1964 đến 2022: phân tích thư mục với cơ sở dữ liệu Scopus - Phạm , Thị Hồng Hạnh; Đỗ , Thị Hồng Liên; Lại , Phương Liên; Đỗ , Thị Trinh (Tạp chí Giáo dục, 2023)
In recent years, career guidance in high schools has received considerable attention, which is reflected in the viewpoints and guidelines in education and policies, contributing to promoting the economies of developed countries. The main objective of this study is to investigate the development of scientific publications in terms of quantity, growth patterns and research trends on career guidance in high schools around the world. We used bibliometric analysis based on VOSviewer software to conduct a review of 382 Scopus-indexed articles and books published between 1964 and March 2022. This study shows that scientific publications on career guidance in high schools have grown steadily in the 21st century, especially from 2010 to present. Recently, the dominant research trend has been the topics related to preparing high school students for career selection; opportunities to create social justice in understanding and deciding on career choices; ways to obtain social resources to support career-orientation activities in high schools.